Pengaruh Fatherless terhadap Pembentukan Identitas dan Kesehatan Mental - Nita Amelia Suryaningtyas; Chariva Aghna Ghaniya; Sri Mulyeni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Fatherlessness is a condition in which individuals grow up without adequate paternal presence or involvement, either physically or emotionally. This condition is not only related to the absence of a father figure within the family structure, but also to the limited role of fathers in providing emotional support, moral guidance, and a sense of security for their children. The phenomenon of fatherlessness has the potential to cause various psychological wounds that affect personality development and mental well-being. This study aims to explore in depth the psychological experiences and forms of emotional distress experienced by fatherless individuals within the environment of Universitas Nasional Pasim Bandung. The study employed a qualitative approach using in-depth interviews with ten informants who had fatherless backgrounds due to divorce, death, or emotional unavailability of the father. The data were analyzed through processes of reduction, categorization, and conclusion drawing to obtain a comprehensive understanding. The findings indicate that the absence of a father has a significant impact on various aspects of psychological development, particularly self-esteem, emotional regulation, identity formation, and patterns of social relationships. Informants tended to experience self-doubt, heightened sensitivity to criticism, confusion regarding life direction, and difficulties in expressing and managing emotions. However, the experience of fatherlessness did not produce uniform effects across individuals. Informants who received strong emotional support from mothers, extended family members, or supportive social environments demonstrated better adaptive abilities in coping with emotional stress and building healthy interpersonal relationships. These findings emphasize that fatherlessness is not merely an issue of a father’s physical absence, but a long-term psychological experience that shapes how individuals perceive themselves, others, and their surroundings.